2021
DOI: 10.2139/ssrn.3817810
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of SARS-CoV-2 Infection in Mice Reveals Neutralizing Antibodies Require Fc Function for Optimal Efficacy

Abstract: Neutralizing antibodies (NAbs) are effective in treating COVID-19 but the mechanism of immune protection is not fully understood. Here, we applied live bioluminescence imaging (BLI) to monitor the real-time effects of NAb treatment in prophylaxis and therapy of K18-hACE2 mice intranasally infected with SARS-CoV-2-nanoluciferase. We visualized sequential spread of virus from the nasal cavity to the lungs followed by systemic spread to various organs including the brain, culminating in death. Highly potent NAbs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…SARS-CoV-1 also showed dissemination to the brain ( 48 ). A recent study showed the ubiquity of SARS-CoV-2 infection in mice and delineated the rapid time course of neuroinvasion ( 49 ). This study also discovered that the Fc portion of antibodies, not just the binding regions, was important for the anti-viral response ( 49 ).…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-1 also showed dissemination to the brain ( 48 ). A recent study showed the ubiquity of SARS-CoV-2 infection in mice and delineated the rapid time course of neuroinvasion ( 49 ). This study also discovered that the Fc portion of antibodies, not just the binding regions, was important for the anti-viral response ( 49 ).…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…A recent study showed the ubiquity of SARS-CoV-2 infection in mice and delineated the rapid time course of neuroinvasion ( 49 ). This study also discovered that the Fc portion of antibodies, not just the binding regions, was important for the anti-viral response ( 49 ). This highlighted that NK cells, macrophages, and neutrophils play a role in clearing the virus dependent on FcR binding involved in antibody-dependent cytotoxicity and phagocytosis and emphasised the consideration needed for the Fc region when developing effective therapeutic antibodies.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%